Family-related adversity and positive youth development: the role of psychological distress, hopelessness and hostility - Jaroslava Mackova; Zuzana Dankulincova Veselska; Daniela Filakovska Bobakova; Andrea Madarasova Geckova; Jitse P. van Dijk; Sijmen A. Reijneveld (BMC Psychology)
Abstract Background The family is a very important institution that provides relationships and contexts for adolescents and can activate a trajectory of their positive development. Family-related adversity can endanger this development via associated negative emotions, such as feelings of hopelessness, hostility, and psychological distress. Therefore, we aimed first to explore the association of family-related adversity with positive youth development (PYD), and second whether psychological distress, hopelessness, and hostility mediate this association. Methods We obtained self-reported data from 308 Slovak adolescents (44.5% were boys, mean age = 12.55). Family-related adversity was measured using questions regarding the death of parents, divorce/separation, violence between parents, and parental substance abuse. Positive youth development was measured with the Very Short PYD questionnaire; psychological distress with the GHQ-12; hopelessness with the Hopelessness questionnaire and hostility with a subscale from the Aggression Questionnaire. Results We found that family-related adversity was not associated with the first PYD component – internal values (regarding the domains of character and caring). However, it was negatively associated with its second component – self- and social efficacy (regarding the domains connection, competence and confidence): regression coefficient B= -0.32; 95%; confidence interval CI: -0.57 to -0.06). Next, we found that psychological distress (0.38; -0.50 to -0.26), hopelessness (-0.18; -0.31 to -0.05) and hostility (-0.23; -0.33 to -0.13) were associated with self- and social efficacy. Moreover, all potential mediators had statistically significant indirect effects: psychological distress − 0.11, hopelessness − 0.09 and hostility − 0.08. Conclusion These findings may provide suggestions for programs supporting adolescents from families in adversity. These could be directed at better coping with psychological distress and addressing hostility and hopelessness.